Rumen ciliate protozoa of domestic sheep (Ovis aries) and goat (Capra aegagrus hircus) in Kyrgyzstan - Gürelli, Gözde; Canbulat, Savaş; Aldayarov, Nurbek; Dehority, Burk A (Oxford University Press (OUP), 2016)
Species composition and concentration of rumen ciliate protozoa were investigated in the rumen contents of 14 domestic sheep and 1 goat living in Bishkek, Kyrgyzstan. This is the first report on rumen ciliates from ruminants living in Kyrgyzstan. In sheep 12 genera, 28 species and 12 morphotypes were detected, whereas in goat 8 genera, 12 species and 4 morphotypes were detected. The density of ciliates in sheep was (28.1 ± 20.0) × 10(4) cells mL(-1) and in goat was 37.0 × 10(4) cells mL(-1). Dasytricha ruminantium, Isotricha prostoma, Entodinium simulans and Ophryoscolex caudatus were major species (100%) in sheep, and for the first time, Diplodinium rangiferi was detected in a domestic goat.
Keywords: Phenotype; Rumen; Sheep; Goats; Animals; Biodiversity; Ciliophora; Kyrgyzstan; Sheep, Domestic; 3. Good health